1998
DOI: 10.1523/jneurosci.18-20-08228.1998
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Potentials Mediated via α-Bungarotoxin-Sensitive Nicotinic Acetylcholine Receptors in Rat Hippocampal Interneurons

Abstract: Exogenous application of acetylcholine elicits inward currents in hippocampal interneurons that are mediated via ␣-bungarotoxin-sensitive nicotinic acetylcholine receptors, but synaptic responses mediated via such receptors have never been reported in mammalian brain. In the present study, EPSCs were evoked in hippocampal interneurons in rat brain slices by electrical stimulation and were recorded by using whole-cell voltage-clamp techniques. Nicotinic EPSCs were isolated pharmacologically, using antagonists t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
247
1
2

Year Published

2000
2000
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(271 citation statements)
references
References 34 publications
18
247
1
2
Order By: Relevance
“…The postsynaptic response is mediated by ␣4␤2-like nAChRs (Dourado and Sargent, 2002). Other examples have now emerged, documenting nicotinic postsynaptic responses involving both ␣7-and non-␣7 nAChRs in the CNS (Zhang et al, 1993;Roerig et al, 1997;Alkondon et al, 1998;Frazier et al, 1998, Hefft et al, 1999Jones et al, 1999). Ultrastructural studies have confirmed that at least ␣4␤2-nAChRs can be found in PSDs in the rat substantia nigra (Arroyo-Jimenez et al, 1999).…”
Section: Postsynaptic/perisynaptic Sitesmentioning
confidence: 98%
See 1 more Smart Citation
“…The postsynaptic response is mediated by ␣4␤2-like nAChRs (Dourado and Sargent, 2002). Other examples have now emerged, documenting nicotinic postsynaptic responses involving both ␣7-and non-␣7 nAChRs in the CNS (Zhang et al, 1993;Roerig et al, 1997;Alkondon et al, 1998;Frazier et al, 1998, Hefft et al, 1999Jones et al, 1999). Ultrastructural studies have confirmed that at least ␣4␤2-nAChRs can be found in PSDs in the rat substantia nigra (Arroyo-Jimenez et al, 1999).…”
Section: Postsynaptic/perisynaptic Sitesmentioning
confidence: 98%
“…Both in the rat hippocampus and in the chick ciliary ganglion ␣7-nAChRs have been shown to generate significant postsynaptic currents (Zhang et al, 1996;Ullian et al, 1997;Frazier et al, 1998). Nonetheless, the receptors appear to be excluded from PSDs on the neurons.…”
Section: Postsynaptic/perisynaptic Sitesmentioning
confidence: 99%
“…The model predicts that high concentrations of ligand will cause complete desensitization (more fractional occupation of nonconducting states); conversely, low concentrations (less occupancy) will allow prolonged channel opening. In terms of the concentrations of agonist effective for desensitization, ␣7*-nAChRs can be effectively desensitized by submicromolar doses of agonist, for example, the IC 50 for desensitization by nicotine is approximately 500 nM in hippocampus (Frazier et al, 1998;McQuiston and Madison, 1999;Alkondon et al, 2000), although in general the desensitized states of ␣7 subunit-containing receptors are much less sensitive to agonist than heteromeric nAChRs. The simple notion that all ␣7*-nAChRs desensitize quickly is challenged by the observation that very slowly desensitizing forms of ␣7/␣BTX-sensitive receptors exist in both peripheral intracardiac ganglion and superior cervical cells (Cuevas and Berg, 1998;Cuevas et al, 2000).…”
Section: Homomeric ␣-Receptorsmentioning
confidence: 99%
“…In the mammalian brain, ␣7 and ␣4␤2 nAChRs control synaptic transmission mediated by the major inhibitory and excitatory neurotransmitters, ␥-aminobutyric acid (GABA) and glutamate, respectively (McMahon et al, 1994;Gray et al, 1996;Lindstrom et al, 1996;Role and Berg, 1996;Albuquerque et al, 1997;Alkondon et al, 1997aAlkondon et al, , 1999Alkondon et al, , 2000cBertolino et al, 1997;Léna and Changeux, 1997;Wonnacott, 1997;Radcliffe and Dani, 1998;Ji and Dani, 2000;Alkondon and Albuquerque, 2001) and mediate fast synaptic transmission (Zhang et al, 1993;Roerig et al, 1997;Alkondon et al, 1998;Frazier et al, 1998;Hatton and Yang, 2002). Certain aspects of neuronal proliferation, differentiation and death, are also modulated by ligands interacting with ␣7 and ␣4␤2 nAChRs in the brain (Berger et al, 1998;Broide and Leslie, 1999;Belluardo et al, 2000;Coronas et al, 2000;Dajas-Bailador et al, 2002;Falk et al, 2002).…”
Section: Introductionmentioning
confidence: 99%